Territorial Links in the Jesuitic-Guaranies Missions of Paraguay, Argentina, and Brazil: A Network Analysis Approach - Gómez, Juan de Dios Páramo (2024)
Relationships and territorial links are fundamental to Geography studies. In recent years, these aspects have undergone significant evolution. Besides, the study of tourism activity is not indifferent since the flows generated in places of tourism interests are those that give rise to territorial dynamics. The main objective of this study is to reveal the spatial interactions stemming from an internationally renowned tourist route, with a very particular niche of its resources, which focus on the heritage of the Jesuit-Guarani missions located in three countries: Paraguay, Argentina, and Brazil. The methodology used integrates the use of qualitative and quantitative techniques. These techniques are combined with "Gephi," a network analysis software, and "Geographic Information Systems" (GIS). With the aid of cartography, the characteristics and properties of the nodes and links established among the “pueblos misionales" in which the primary tourist activities take place are displayed. Additionally, the concept of "friction of space" is incorporated to explain, in more detail, each of the relationships and links established.